A experiência de adaptação de mães de crianças e adolescentes com paralisia cerebral: Um estudo qualitativo - Inês Martins Mimoso; Luciana Sotero; Ana Isabel Cunha; Juliana Maia de Queiróz (2021)
Cerebral palsy (CP) is one of the most common chronic pediatric conditions worldwide, raising multiple challenges on the family, particularly, on mothers, who assume most of the care that the child needs. Nevertheless, despite the demands associated with the care of the child, the literature has been showing that parents also have the competence to face adversity. Goals: Understand the experience of these mothers, exploring the factors that, in their perception, contribute to a positive adaptation. Methods: A qualitative study was conducted, using semi-structured interviews, with six mothers of children/adolescents with CP. The present data were analysed using a thematic analysis. Results: Five major themes were identified that highlight important factors for the adaptation: (1) intrafamily cooperation; (2) support network; (3) perception of competence; (4) put the PC “in its place”; e (5) maintenance of a positive outlook. Conclusions: The identification of these themes allows us to highlight the strengths and resources associated with an adaptive trajectory of mothers of children/adolescents with CP, translating into clues for clinical intervention and a starting point for future investigations.